2021
DOI: 10.3389/fcell.2021.749490
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage Repair Deficiency in Pancreatic Ductal Adenocarcinoma: Preclinical Models and Clinical Perspectives

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal cancers worldwide, and survival rates have barely improved in decades. In the era of precision medicine, treatment strategies tailored to disease mutations have revolutionized cancer therapy. Next generation sequencing has found that up to a third of all PDAC tumors contain deleterious mutations in DNA damage repair (DDR) genes, highlighting the importance of these genes in PDAC. The mechanisms by which DDR gene mutations promote tumorigenesis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 96 publications
(145 reference statements)
0
10
0
Order By: Relevance
“…HR wild-type pancreatic cancer cell lines, e.g., Panc-1, MIAPaCa-2, and Panc02, were used to test whether our strategy would be efficacious for PDAC patients that do not harbor HR-related mutations. 45 Colony formation assay showed that in Panc-1, MIAPaCa-2, Panc02, and KPC-A548 cells, the half-maximal inhibitory concentration (IC 50 ) of Olaparib ranged from 1.0 to 20.6 μM, and the IC 50 values of AZD0156 were between 0.03 and 5.3 μM (Figure S7). The two drugs were first screened for their optimal dose ratios in the absence of electroporation (Figure 2A).…”
Section: Preparation and Characterization Of Ros-responsivementioning
confidence: 99%
“…HR wild-type pancreatic cancer cell lines, e.g., Panc-1, MIAPaCa-2, and Panc02, were used to test whether our strategy would be efficacious for PDAC patients that do not harbor HR-related mutations. 45 Colony formation assay showed that in Panc-1, MIAPaCa-2, Panc02, and KPC-A548 cells, the half-maximal inhibitory concentration (IC 50 ) of Olaparib ranged from 1.0 to 20.6 μM, and the IC 50 values of AZD0156 were between 0.03 and 5.3 μM (Figure S7). The two drugs were first screened for their optimal dose ratios in the absence of electroporation (Figure 2A).…”
Section: Preparation and Characterization Of Ros-responsivementioning
confidence: 99%
“…The non-homologically repairable damage includes plain NHEJ and all the mechanisms to the left of it in the lower half of the Figure 2a. The TP53 sensory layer between damage and repair is shown in more detail in Figure 3a describing the wide range of sensory proteins and cellular response mechanisms (Figure 2a developed from [1,9,33,34]).…”
Section: Figurementioning
confidence: 99%
“…The non-homologically repairable damage includes plain NHEJ and all the mechanisms to the left of it in the lower half of the Figure 2a. The TP53 sensory layer between damage and repair is shown in more detail in Figure 3a describing the wide range of sensory proteins and cellular response mechanisms (Figure 2a developed from [1,9,33,34]). The speed of the Ku-DNApk heterodimer complex and TP53 recruitment to a DNA DSB, a few seconds, makes it the most likely starting point of all DSBs absolutely necessary not to lose the right order in which the DNA ends belong together (horizontal blue arrow NHEJ->HR "switch" when p53 senses repair problems as in Figure 10 [1,4,9,17,27]).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“… 2, 3 ). Such molecular defects can advocate for promising targeted therapies ( 4 ) as transcriptomic signatures of high replication stress predict response to ATR and WEE1 inhibitors in preclinical models ( 5 ). More importantly, patients with germline mutations in the BRCA2 gene were recently found to benefit from first-line platinum-based FOLFIRINOX regimen followed by PARP inhibitors treatment ( 6 ).…”
Section: Introductionmentioning
confidence: 99%